2021
DOI: 10.1017/s0714980821000635
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Primary Care Models of Dementia Care that Improve Quality of Life for People Living with Dementia and their Care Partners: An Environmental Scan

Abstract: Dementia is a growing concern in Canada, affecting peoples’ health and raising the cost of care. Between June and October 2019, we conducted an environmental scan to identify primary care models, strategies, and resources for dementia care from 11 pre-selected countries and assess their impact on quality-of-life measures. Search strategies included a rapid scoping review, grey literature search, and discussions with stakeholders. Eighteen primary care-based models of dementia care were identified. Common facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Strategies and interdisciplinary models of primary care to address the issue of timely diagnosis vary by province ( 7 9 ). Some of these models that can help to address the issue of timely diagnosis include MINT Memory Clinics and family health teams (ON) ( https://www.hqontario.ca/Quality-Improvement/Quality-Improvement-in-Action/ARTIC/ARTIC-Projects/Primary-Care-Collaborative-Memory-Clinics ), the Rural and Remote Memory Care Clinic (RRMC) in Saskatchewan ( https://cchsa-ccssma.usask.ca/ruraldementiacare/ ) ( 10 ), family medicine groups (QC), and Primary Care Networks (AB).…”
Section: Current Landscape Of the Diagnosis And Management Of Ad In P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies and interdisciplinary models of primary care to address the issue of timely diagnosis vary by province ( 7 9 ). Some of these models that can help to address the issue of timely diagnosis include MINT Memory Clinics and family health teams (ON) ( https://www.hqontario.ca/Quality-Improvement/Quality-Improvement-in-Action/ARTIC/ARTIC-Projects/Primary-Care-Collaborative-Memory-Clinics ), the Rural and Remote Memory Care Clinic (RRMC) in Saskatchewan ( https://cchsa-ccssma.usask.ca/ruraldementiacare/ ) ( 10 ), family medicine groups (QC), and Primary Care Networks (AB).…”
Section: Current Landscape Of the Diagnosis And Management Of Ad In P...mentioning
confidence: 99%
“…This study identified 18 different primary care-based models of dementia care for persons in the early and middle stages of dementia. However, despite 5 of Canada's provinces and territories having dementia strategies (British Columbia, Alberta, Manitoba, Quebec and Nova Scotia), only 2 primary care memory clinic models have been implemented in Canada ( 9 ). The Primary Care Collaborative Memory Clinics (PCCMC) service delivery model integrates interprofessional healthcare providers into primary care settings, and partners with community agencies to meet the multifaceted needs of the dementia population.…”
Section: Current Landscape Of the Diagnosis And Management Of Ad In P...mentioning
confidence: 99%